Evaluation of Timing Side-Channel Leakage on a Multiple-Target Dynamic Binary Translator - Napoli, Otávio O.; do Rosario, Vanderson Martins; Aranha, Diego F.; Borin, Edson (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2018)
Timing side-channel attacks are an important issue for cryptographic algorithms. If the execution time of an implementation depends on secret information, an adversary may recover the latter through measuring the former. Different approaches have emerged recently to exploit information leakage on cryptographic implementations and to protect them against these attacks. However, little has been said about ISA emulation and its impact on timing attacks. In this paper, we investigate the impact of an emulator (dynamic binary translator), OI-DBT, using different Region Formation Techniques (RFTs) on constant-time and non-constant-time implementations of cryptographic algorithms. We show that emulation can have a significant impact on secret leakages, even mitigating them in some cases. Moreover, our results indicate that the choice of RFT heuristic by the emulator does have an impact on these leakages.